3D printed hydrogel based on M-CMC and PNIPAM with ZIF-8 nanoparticles: optimization for responsive swelling behaviors - Li, Yujia (Nanyang Technological University, 2023)
This study focuses on the development of an interpenetrating polymer network (IPN) hydrogel using carboxymethyl cellulose methacrylate (M-CMC) and poly(N-isopropylacrylamide) (PNIPAM) via digital light processing (DLP) 3D printing. DLP 3D printing allowed for the customization of M-CMC/PNIPAM hydrogels with different properties by controlling layer thickness and curing time, resulting in optimized swelling behaviors. Moreover, we incorporated a type of metal-organic framework (MOF) nanoparticles, zeolitic imidazolate framework-8 (ZIF-8) and investigated the effects of its concentration as well as the temperature on the swelling, deswelling, and reswelling behaviors of M-CMC/PNIPAM IPN hydrogels. As a result, the hydrogel containing 0.5 wt% ZIF-8 exhibited superior performance in terms of swelling kinetics and temperature responsiveness compared to hydrogels with other ZIF-8 concentrations and non-ZIF-8 hydrogels. Our M-CMC/PNIPAM hydrogels showed a swelling degree of 5000% when ZIF-8 was 0.5 wt% during the first 3 hours of swelling in deionized water at T = 25 °C, exceeding the results of other concentrations. We explored the thermo-responsive swelling behaviors of M-CMC/PNIPAM hydrogels based on the temperature-sensitive properties of PNIPAM, which exhibits hydrophilicity below 32 °C and hydrophobicity over 32 °C. ZIF-8 nanoparticles were found to enhance swelling properties due to their large surface area and high porosity, which allowed for better water entrapment within the hydrogel network. An optimal ZIF-8 concentration of 0.5 wt% was identified, as higher concentrations led to particle aggregation, negatively affecting swelling properties. Furthermore, the hydrogel with 0.5 wt% ZIF-8 demonstrated the lowest water retention during the deswelling process and the fastest water uptake during reswelling, indicating its potential for reusability. These findings, along with the hydrogel’s temperature responsive performances, offer valuable insights into the development of smart, responsive hydrogels via 3D printing for various applications, particularly in soil water storage.